An adaptive user interface model for enhancing usability and performance efficiency of diabetes mobile applications / Chew Sook Peng - Chew , Sook Peng (2022)
There are many ways to promote patient empowerment and technology is one of them. With the help of eHealth and mHealth, patient empowerment has become more convenient and effective as patients will have the control of monitoring their own health care right at their fingertips, especially for those with chronic diseases like diabetes. As per the National Diabetes Registry Report published in 2020, there was an estimate of 3.9 million adults having raised blood glucose in 2019 and there is a huge number of diabetes patients in our country. There are many diabetes mobile applications from the iOS App Store and Google Playstore, but these apps are not usable enough to promote patient empowerment. For example, a previous research in 2021 reported a few shortcomings of two popular diabetes applications, namely mySugr and Glucose Buddies. The users found the apps too time consuming and too complex to use. There were too many features in the app. The participants also reported wanting customized notifications related to their diabetes management goal. Usability is a key factor in influencing whether the user will engage with the mHealth app. Previous research suggested that the user experience can be enhanced with adaptive user interface (AUI). With AUI, users will be able to have better control in self-care and self-management of their diseases. Context-based and rulebased AUI has proven to improve user experience of a hypoglycemia emergency care mobile applications but there was no research to ascertain whether AUI improves the user experience and usability of a diabetes self-care mobile application. The objective of this research is to propose and design a Diabetes Mellitus AUI Model with Role-Based UI Simplification (RBUIS) that allows different diabetes mobile apps users to personalize the apps’ user interface based on their preference and specification. The model aims at providing an efficient and usable application for better diabetes self-care and selfmanagement. An AUI engine built upon the model enables processing data collected from user profile and providing a personalized user experience based on their needs and goals. An experiment done concluded that AUI performs better in user experience and usability as compared to non-AUI. Results of the experiment showed that the application with AUI integration showed a more positive result compared to non-AUI in terms of shorter time to perform an action and easier data entry through suggestive data input; and recommended function to be used in the home screen. The application of AUI has also reduced the complexity of the app usage by only displaying the necessary functions to the user. According to the System Usability Scale (SUS) analysis, the application when integrated with AUI achieved the score of “Excellent” while when having AUI disabled only achieved the score of “Good”.